Building clinically actionable models for predicting mechanical complications in postoperatively well-aligned adult spinal deformity patients using XGBoost algorithm. (2023) - Balaban, Baris; Yilgor, Caglar; Yucekul, Altug; Zulemyan, Tais; Obeid, Ibrahim; Pizones, Javier; Kleinstueck, Frank; Perez-Grueso, Francisco Javier Sanchez; Pellise, Ferran; Alanay, Ahmet; Sezerman, Osman Ugur; ,
Highlights: Clinically actionable model to predict complications in spinal deformity surgeries. Key factors of predicting complications in postoperatively well-aligned patients. The location of the lower-instrumented vertebra is the most important feature.